2020
DOI: 10.22541/au.160391060.01177782/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biophysical Basis of Thermometry Limitations to Control COVID-19 are Overcome at Transmissive Skin Overlying Brain-eyelid Thermal Tunnels

Abstract: This a preprint and has not been peer reviewed. Data may be preliminary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The non-invasive nature of the infrared thermography method makes it suitable for mass screening and monitoring in various settings, such as schools, public transport, and healthcare facilities. Rapid and accurate temperature assessment can help identify potential cases of fever early on, enabling timely isolation, testing, and treatment, thus reducing the risk of disease transmission [8,12]. Additionally, the use of the BTT • method can enhance the precision of fever monitoring in pediatric patients, aiding in the prompt diagnosis and management of infectious diseases, including those with atypical presentations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The non-invasive nature of the infrared thermography method makes it suitable for mass screening and monitoring in various settings, such as schools, public transport, and healthcare facilities. Rapid and accurate temperature assessment can help identify potential cases of fever early on, enabling timely isolation, testing, and treatment, thus reducing the risk of disease transmission [8,12]. Additionally, the use of the BTT • method can enhance the precision of fever monitoring in pediatric patients, aiding in the prompt diagnosis and management of infectious diseases, including those with atypical presentations.…”
Section: Discussionmentioning
confidence: 99%
“…During the 2003 SARS outbreak, the BTT • was identified by a Yale University research group and was described as a thermophysical path providing a metric consistent with the Stefan-Boltzmann law of black body radiance [32]. Some authors have shown that the BTT • provides a consistent volumetric heat capacity, resulting in a more accurate assessment of fever from the hypothalamic thermoregulatory center [12]. This is particularly important during the COVID-19 pandemic, where suboptimal thermometry may result in the misdiagnosis of children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations